2017
DOI: 10.1111/jopr.12610
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐Based Investigation of Denture Sonication Method in Patients with Candida‐Associated Denture Stomatitis

Abstract: The denture sonication method is easy, accurate, and sensitive, and increases the possibility of diagnosing patients with Candida-associated DS. Additionally, yeast quantification, mixed Candida spp., and non-albicans Candida were detectable when cultivation on Candida CHROMagar was performed. It was not possible using conventional methods, such as swab or oral rinse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Serbia has a large older population; almost 20% are older than 65 years (1,352,948 population size). In this group about 15% of the population wear dentures (202,942 cases), and our laboratory based investigation showed a prevalence of Candida stomatitis of 32.8% [ 25 ], which makes for 66,991 OC cases in denture wearers. Also, severe Candida -related prosthetic stomatitis (Newton classification—severity type III) was found in 18.3% cases and was mainly associated with mixed Candida spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serbia has a large older population; almost 20% are older than 65 years (1,352,948 population size). In this group about 15% of the population wear dentures (202,942 cases), and our laboratory based investigation showed a prevalence of Candida stomatitis of 32.8% [ 25 ], which makes for 66,991 OC cases in denture wearers. Also, severe Candida -related prosthetic stomatitis (Newton classification—severity type III) was found in 18.3% cases and was mainly associated with mixed Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…Also, severe Candida -related prosthetic stomatitis (Newton classification—severity type III) was found in 18.3% cases and was mainly associated with mixed Candida spp. or NAC strains which can be difficult to treat [ 25 ]. The incidence data for OC following antibiotic or corticosteroid usage is difficult to estimate.…”
Section: Resultsmentioning
confidence: 99%
“…The choice for the microorganisms to be tested was based in the main goal of the membrane application, that is, the control of oral microbiota: S. mutans (present in the dental biofilm and main microorganism of caries lesion) (25)(26) and C. albicans (main microorganism of oral mucosa infections in adult wearers of prostheses) (27).…”
Section: Discussionmentioning
confidence: 99%
“…For cases with denture stomatitis, yeast quantification of mixed Candida spp., and non-albicans Candida using ultrasonication sampling produced better results. This was not possible when using conventional methods, such as swab or oral rinse sampling procedures [16]. The aim of this comparative study was fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…This is easier and less subjective than surface swabs or denture material retrieval, sectioning, and then culturing [15]. Studies, which focused on the denture stomatitis cases, found that sampling from sonication fluids is accurate, sensitive, and increases the possibility of diagnosing patients with candida-associated lesions [16].…”
Section: Introductionmentioning
confidence: 99%